DEPRESSION AND QUALITY OF LIFE AMONG LEUKEMIA PATIENTS AT TEACHING HOSPITAL IN KELANTAN, MALAYSIA - Nur Fakhriyah Razali; Nur Adibah Solihin Sulaiman, (The Malaysian Journal of Nursing (MJN), 2021)
Leukemia is cancer that begins to develop in blood cells, producing abnormal cells. Depression is the most common symptom encountered by leukemia patients. Depression experienced by leukemia patients is not the same as that experienced by normal people daily, and it affects different aspects of quality of life (QOL). Aim: This study is designed to determine the level of depression and quality of life among leukemia patients at a teaching university in Kelantan, Malaysia. Methodology: A descriptive cross-sectional design was conducted among leukemia patients at a teaching hospital in Kelantan, Malaysia, using self-administered questionnaires. A total of 40 patients was selected using a random sampling technique. Results: Most of the participants in this study had a higher level of depression (87.5%). However, the overalls level of quality of life in this study was good with the highest mean of domain scales. Conclusion and Recommendations: The study results can be used as baseline information to determine the level of depression and level of quality of life among leukemia patients in Malaysia health care settings. Nurses play an essential role in helping leukemia patients manage their depression not to affect their quality of life.